Efek Ekstrak Daun Oregano (Origanum vulgare) terhadap Plat Resin Akrilik Heat-Cured yang Dikontaminasi Candida albicans dan Streptococcus mutans - Silvia Naliani; Shelly Lelyana; Henry Y. Mandalas; Jason F. Laurence; Vinna K. Sugiaman; Jane A. V. Wibisono; Dian Lesmana (e-GiGi, 2023)
Abstract: Long-term use of dentures with poor cleaning can cause denture stomatitis mainly due to Candida albicans and Streptococcus mutans. Oregano leaf (Origanum vulgare) which contains a variety of active components is believed to be an alternative of denture cleansers. This study aimed to determine the effect of oregano leaf extract on heat-cured acrylic resin plates contaminated with C. albicans and S. mutans. There were 27 heat-cured acrylic plates contaminated and soaked for 10 minutes in nine treatment groups, as follows: oregano leaf extract of 50 mg/ml, 25 mg/ml, 12.5 mg/ml, 6.25 mg/ml, 3,125 mg /ml, 1,562 mg/ml, and 0,781 mg/ml, distilled water as the negative control, Polident denture cleanser fresh (positive control for C. albicans) and chlorhexidine gluconate 0,2% (positive control for S. mutans). The colony number of C. albicans and the inhibition zones of S. mutans were counted. The results showed that the lowest number of C. albicans colony and the largest inhibition zone for S. mutans were at the concentration of 50 mg/ml oregano leaf extract. In conclusion, there was an effect of oregano leaf extract on acrylic resin plates contaminated with Candida albicans and Streptococcus mutans. Keywords: acrylic resin; denture stomatitis; Origanum vulgare; Candida albicans; Streptococcus mutans   Abstrak: Penggunaan gigi tiruan secara terus menerus dalam jangka panjang dengan pembersihan yang buruk dapat menyebabkan denture stomatitis terutama oleh Candida albicans dan Strepto-coccus mutans. Daun oregano (Origanum vulgare) yang mengandung beragam komponen aktif diyakini dapat menjadi alternatif pembersih gigi tiruan. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak daun oregano terhadap plat resin akrilik heat-cured yang dikontaminasi jamur C. albicans dan S. mutans. Terdapat 27 plat akrilik heat-cured yang dikontaminasi dan dilakukan perendaman selama 10 menit dalam sembilan kelompok perlakuan yaitu, konsentrasi ekstrak daun oregano 50 mg/ml, 25 mg/ml, 12,5 mg/ml, 6,25 mg/ml, 3,125 mg/ml, 1,562 mg/ml, 0,781 mg/ml, akuades (kontrol negatif), Polident Denture Cleanser Fresh (kontrol positif C. albicans), dan chlorhexidine gluconate 0,2% (kon-trol positif S. mutans). Jumlah koloni C. albicans dan zona hambat S. mutans dihitung. Hasil penelitian menunjukkan jumlah koloni C. albicans terkecil dan zona hambat S. mutans terbesar pada konsentrasi ekstrak daun oregano 50 mg/ml. Simpulan penelitian ini ialah terdapat pengaruh ekstrak daun oregano terhadap plat resin akrilik yang dikontaminasi Candida albicans dan Streptococcus mutans. Kata kunci: resin akrilik; denture stomatitis; Origanum vulgare; Candida albicans; Streptococcus mutans